Teologi Ziarah dalam Kumpulan Mazmur Ziarah: Makna dan Praksis bagi Orang Percaya Masa Kini - David Eko Setiawan; Dwi Ratna (Sekolah Tinggi Teologi Anugrah Indonesia, 2022)
In the book of Psalms there is a collection of pilgrimage psalms that are interesting to study, because they contain deep meanings and praxis that are still relevant today. The collection of pilgrimage psalms is not just ancient texts that have no link to the lives of today's believers, but in them are rich in meaning and praxis for them. This article aims to find the meaning and praxis of pilgrimage theology contained in the collection of Pilgrimage Psalms. The research problem in this article is what is the meaning and praxis of Pilgrimage Theology in the collection of Pilgrimage Psalms for today's believers? The methods used in this study are hermeneutics and literature methods. The results of this study are as follows, Pilgrimage Theology in the collection of Pilgrimage Psalms contains the meaning: First, the theological understanding of God. Second, an understanding of the city of Jerusalem. Third, an understanding of the inner attitude in worship. Fourth, the understanding of blessing, fifth, the understanding of prayer/singing. The praxis of Pilgrimage Theology are as follows; First, encourage respect for God as the source of all things for His People. Second, hold fast to God's promise like His faithfulness to Jerusalem. Third, convert today's believers from the wrong attitude in worship. Fourth, correct the wrong concept of the origin and nature of blessing. Fifth, practice prayer and thanksgiving properly. AbstrakDi dalam kitab Mazmur terdapat kumpulan mazmur ziarah yang menarik untuk ditelaah, karena mengandung makna yang dalam serta praksis yang masih relevan sampai masa kini. Kumpulan mazmur ziarah tersebut bukan sekedar teks-teks kuno yang tidak memiliki tautan dengan kehidupan orang percaya masa kini, malahan di dalamnya kaya dengan makna dan praksis bagi mereka. Artikel ini bertujuan untuk menemukan makna dan praksis dari Teologi Ziarah yang terdapat dalam kumpulan Mazmur Ziarah. Masalah penelitian dalam artikel ini adalah apakah makna dan praksis Teologi Ziarah dalam kumpulan Mazmur Ziarah bagi orang percaya masa kini? Metode yang digunakan dalam penelitian ini adalah metode hermeneutika dan kepustakaan. Hasil dari penelitian ini adalah sebagai berikut, Teologi Ziarah dalam kumpulan Mazmur Ziarah mengandung makna: Pertama,pemahaman teologis tentang TUHAN. Kedua, pemahaman tentang kota Yerusalem. Ketiga, pemahaman tentang sikap batin dalam beribadah. Keempat, pemahaman tentang berkat, Kelima, pemahaman tentang doa dan nyanyian syukur. Adapun praksis dari Teologi Ziarah adalah sebagai berikut; Pertama, dorong rasa hormat terhadap Allah sebagai sumber segala sesuatu bagi Umat-Nya. Kedua, memegang teguh janji Allah seperti kesetiaan-Nya terhadap Yerusalem. Ketiga, mempertobatkan orang percaya masa kini dari sikap yang salah di dalam ibadah. Keempat, mengoreksi konsep yang salah tentang asal dan hakikat berkat. Kelima, mempraktikkan doa dan nyanyian syukur dengan benar.Kata Kunci: Teologi Ziarah, Mazmur Ziarah, Makna. Praksis